Coupled thermo-hydro-mechanical modelling for geothermal doublet system with 3D fractal fracture - Liu, Jia; Xue, Yi; Zhang, Qi; Wang, Huimin; Wang, Songhe (Applied thermal engineering, 2022)
•3D fractal fracture existed in a geothermal doublet system.•Coupled thermo-hydro-mechanical interaction for bedrock and fracture.•Normal and shear deformations of fracture based on thin elastic layer assumption.•Evaluation of thermal breakthrough due to preferential fracture flow. The existence of preferential flow paths, such as fractures and/or fault play an vital role on the thermal breakthrough of geothermal doublet system. The interaction between the preferential flow path and bedrock is often uneven and may have typical fractal characteristic. This study proposes a thermo-hydro-mechanical coupling model considering the deformation of fractal fractures. The fractal fracture is regarded as a thin elastic layer existed in the bedrock, whoes deformation depends to the bedrock and its own mechanical properties. Subsequently, the geothermal doublet system with a three-dimensional fractal fracture is modelled and the parameters affecting thermal breakthrough are investigated numerically. Research results indicate that the thin elastic layer assumption is remarkably robust for modelling fracture opening and closing under coupling conditions. Owing to complex fracture geometry, the fracture permeability evolution presents certain heterogeneity, which is related to fractal dimension, in-situ stress, and geothermal wells layout. The cool water in fracture with larger fractal dimension can interact with the bedrock more fully and further affect the thermal breakthrough. This further suggests that the site selection of geothermal wells should consider the specific geometry of preferential flow paths to avoid premature thermal breakthrough inducing low system efficiency.